2022
DOI: 10.3390/ijerph192315494
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effect of Air Pollution on Human Microbial Community and Bacterial Flora: A Short Review

Abstract: A balanced microbiota composition is requisite for normal physiological functions of the human body. However, several environmental factors such as air pollutants may perturb the human microbiota composition. It is noticeable that currently around 99% of the world’s population is breathing polluted air. Air pollution’s debilitating health impacts have been studied scrupulously, including in the human gut microbiota. Nevertheless, air pollution’s impact on other microbiotas of the human body is less understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 117 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…There are several reports where it has been found that regular burning of incense may affect the normal microflora of human beings, especially the oral ones, this could be used as a primary biomarker for incense-related health issues and impact. [23,167,168] There are several reports where smoke released from a cigarette or due to smoking has affected the normal microflora of humans, [18] for instance, a team led by Gui reported the effect of cigarette smoking on the gut microflora, [169] while a team led by Kubota studied the effect of smoking on the subgingival microflora of patients of periodontitis in Japan where the investigators concluded that Camplylobacter rectus was more prevalent among smokers in comparison to non-smokers. Further, they also reported that A. actinomycetemcomitans was lower in smokers than the non-smokers.…”
Section: Effect Of Incense Smoke and Particulate Matter On Normal Mic...mentioning
confidence: 99%
“…There are several reports where it has been found that regular burning of incense may affect the normal microflora of human beings, especially the oral ones, this could be used as a primary biomarker for incense-related health issues and impact. [23,167,168] There are several reports where smoke released from a cigarette or due to smoking has affected the normal microflora of humans, [18] for instance, a team led by Gui reported the effect of cigarette smoking on the gut microflora, [169] while a team led by Kubota studied the effect of smoking on the subgingival microflora of patients of periodontitis in Japan where the investigators concluded that Camplylobacter rectus was more prevalent among smokers in comparison to non-smokers. Further, they also reported that A. actinomycetemcomitans was lower in smokers than the non-smokers.…”
Section: Effect Of Incense Smoke and Particulate Matter On Normal Mic...mentioning
confidence: 99%
“…Four factors, including Na 2 SiO 3 concentration, curing time (ct) at 120 and 250 • C, and CFA to slag ratios, have been discovered to affect the bending strength of the material based on the results of the Plackett-Burman study and the steepest ascent test, i.e., 2.2.5 h (ct at 120 • C) and 2.32 h. Despite being substantial pollution, CFA from coal-fired power stations can be utilized in agriculture as a soil-improving agent to boost plant biomass and output. The effect of CFA treatment on plant biomass and the accumulation of beneficial and detrimental components in plants, however, are unknown [67]. A thorough meta-analysis based on 88 publications was performed by Yu, et al, (2019) to assess the effects on plant biomass and 21 element levels in plants as a result of CFA treatment.…”
Section: Cfa For Geopolymersmentioning
confidence: 99%
“…( Robati et al, 2016 ). The biological methods involve the utilization of microorganisms ( Gupta et al, 2022 ) for dye remediation, either in the natural sites or in the bioreactor in the laboratory ( Das & Mishra, 2017 ). The biological approach also involves biosorbents for the remediation of dyes from wastewater ( Cui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%